THEMATIC FIELD SCHOOL OF SHALLOT COMMODITY AS AN AGRICULTUREAL EXTENSION METHODE TO IMPROVE FARMERS, KNOWLEDGE, ATTITUDES, SKILLS AND PRODUCTIVITY - Rahyunanto, Setyo; Sepfrian, Bimoseno (LPPM Universitas Duta Bangsa Surakarta, 2025)
Extension agriculture have important role? for development source Power man agriculture in development agriculture that aims For increase knowledge , attitude , skills And product activity results . Various method extension Already implemented in activity the including school roomy thematic based? approach participatory . Study This aim For know school roomy thematic commodities shallot as method counseling agriculture For increase knowledge , attitude , skills And productivity result . Method study is qualitative descriptive . Informant on study This a total of 30 farmers participant school field . Results study show that school roomy thematic commodities shallot cause a number of matter namely , farmers shallot show category very agree that school roomy increase knowledge And previous skills? they Not yet understand or know . In improvement attitude And productivity results , showing category agree . Recommendation results study is implementation extension agriculture based on participatory with method school roomy thematic more developed again with adapt need farmer .